Powerty alleviation and gender relations in fisheries methodological challenges (Danyag : Journal of Humanities and Social Sciences, 2003)
The paper reviewed local empirical studies on gender relations in fisheries. The studies were conducted between 1985 and 2003 and had an explicit description of the research method used. The aim of the review was to examine the methods used by analyzing their epistemological basis in the context of contributing to poverty alleviation. Many of the studies reviewed utilized the survey method based on a positivist epistemology. These studies showed the different roles of women and men in production, processing, marketing and related concerns. Some studies used qualitative methods with modest attempts to get at the subjective meanings of different activities for women and men in the situations studies as required by an interpretive epistemology. A few studies analyzed gender-based participation in contributing to poverty alleviation. These studies comprise an initial step toward a bigger stride for a critical epistemology. The paper concludes by identifying the methodological challenges for studies on gender relations in fisheries if these are to contribute to poverty alleviation.